2018
DOI: 10.1063/1.5045207
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical rectification and optical bistability in a coupled asymmetric quantum dot-metal nanoparticle hybrid

Abstract: We study the optical response of a coupled asymmetric semiconductor quantum dot-spherical metal nanoparticle structure. The asymmetric quantum dot has permanent electric dipole moments that also interact with light. We derive the density matrix equations for the system including the modification of the electric field and the exciton-plasmon coupling. We emphasize on the effects of the nonlinear optical rectification and controlled optical bistability and analyze these phenomena for different values of the ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 66 publications
(89 reference statements)
0
20
0
Order By: Relevance
“…An active research topic within the field of quantum plasmonics [ 1 , 2 ] is the efficient population control of the exciton and biexciton states in semiconductor quantum dots (SQD) closely placed to metallic nanoparticles (MNP) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For these hybrid nanostructures the population dynamics is rather different compared to the case of a single SQD, since the presence of the MNP amplifies the external electric field and induces interaction between SQD excitons and localized surface plasmons [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An active research topic within the field of quantum plasmonics [ 1 , 2 ] is the efficient population control of the exciton and biexciton states in semiconductor quantum dots (SQD) closely placed to metallic nanoparticles (MNP) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For these hybrid nanostructures the population dynamics is rather different compared to the case of a single SQD, since the presence of the MNP amplifies the external electric field and induces interaction between SQD excitons and localized surface plasmons [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For these hybrid nanostructures the population dynamics is rather different compared to the case of a single SQD, since the presence of the MNP amplifies the external electric field and induces interaction between SQD excitons and localized surface plasmons [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. A great portion of studies in this area is devoted to population transfer between the ground and single exciton states of the SQD, using external fields and with the MNP present [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 12 , 13 , 14 , 16 ]. In many of these works it is reported that the MNP substantially modifies the period of Rabi oscillations between these states [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ], which can even be destroyed for specific SQD-MNP distances [ 4 , 5 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In current studies in photonics, coupled structures formed from semiconductor quantum dots and metal particles at the nanoscale play an important role as they give, in many cases, enhanced optical properties in comparison to individual SQDs and MNPs [1]. The coupling of the excitons to plasmons is responsible for the emergence of interesting optical effects from the SQD-MNP structures, including altered excitonic Rabi oscillations [2][3][4], creation and control of optical bistability and multistability [5][6][7][8][9], population transfer to the exciton [10][11][12][13][14] or biexciton state with high accuracy [15][16][17], controlled slow light [18], creation of gain without inversion [19][20][21], strong enhancement of second harmonic generation [22], and strong modification of four-wave mixing, as well as self-or cross-Kerr nonlinearity [23][24][25][26], control of resonance fluorescence [27][28][29][30], and several others [31][32][33][34][35][36][37][38]. These effects can find applications in the construction of efficient optical devices which can be implemented in the fields of nanophotonics and quantum technology.…”
Section: Introductionmentioning
confidence: 99%
“…Various phenomena have been studied in such media, including the manipulation of spontaneous emission [13][14][15][16], Fano effects in energy absorption [17][18][19][20], slow light and optical transparency [21][22][23], enhancement of the refractive index [24], modification and enhancement of the Kerr nonlinearity [25][26][27][28], four-wave-mixing [29,30], inversionless gain [31][32][33][34][35][36], OB or optical multistability (OM) [37][38][39][40][41][42][43][44][45][46][47][48][49], and many others [50][51][52]. The contemporary fabrication methods [53][54][55][56] for realizing plasmonic nanostructures incorporating quantum emitters [57] enable the experimental verification of the above phenomena.…”
Section: Introductionmentioning
confidence: 99%